Isolation of monoclonal antibodies that recognize the transforming proteins of avian sarcoma viruses. - Lipsich, L A (1983)
Thirteen clones of hybrid cells which synthesize antibodies directed against the Rous sarcoma virus (RSV) transforming protein, pp60src, were isolated. Mouse myeloma cells were fused with spleen cells from mice that had been immunized with purified pp60src from bacterial recombinants which direct the synthesis of the RSV src gene. The hybridomas which survived the selection medium were screened by immunoprecipitation of pp60src from 32P-labeled lysates of RSV-transformed cells. Monoclonal antibodies produced by subclones derived from 13 hybridomas recognized pp60src encoded by the Schmidt-Ruppin and Prague strains of RSV and the cellular homolog of pp60src. Antibody from clone 261 had a high affinity for the viral yes gene product, and antibodies from clones 443 and 463 recognized the transforming proteins encoded by viruses containing the related transforming genes fps and ros. Several other clones had a low affinity for the viral yes, fps, and ros gene products which could be detected by in vitro phosphorylation of the transforming proteins after immunoprecipitation with the monoclonal antibody. All of the monoclonal antibodies allowed phosphorylation of pp60src and casein in an immune complex-bound reaction.